Six new species of Amblypsilopus Bigot (Diptera: Dolichopodidae: Sciapodinae) and a key to species of the Afrotropical mainland - Grichanov, Igor Ya. (European Journal of Taxonomy, 2022)
Six new species of Amblypsilopus Bigot, 1888 from the Afrotropical region are described and illustrated: A. gabonensis sp. nov. from Gabon, A. martini sp. nov., A. mufindiensis sp. nov. and A. udzungwensis sp. nov. from Tanzania, A. milleri sp. nov. from South Africa, and A. spiniscapus sp. nov. from Ivory Coast. Amblypsilopus gabonensis sp. nov. and A. spiniscapus sp. nov. are remarkable in having a setose antennal scape. Amblypsilopus martini sp. nov. and A. mufindiensis sp. nov. are peculiar in bearing very long setae on the antennal pedicel, mesonotum and scutellum. Amblypsilopus milleri sp. nov. is considered a member of the South African A. fasciatus species group despite its unmodified wing venation. The new species differ also from other similar representatives of the genus in the morphology of the male cercus and the male secondary sexual characters on the legs. The male of A. bevisi (Curran, 1927) is described for the first time. The following species described from females are considered doubtful (nomina dubia): A. flavicollis (Becker, 1923), A. rectangularis (Parent, 1937), A. sudanensis (Parent, 1939) and A. tropicalis (Parent, 1933). Amblypsilopus subfascipennis (Curran, 1926) has a strongly sinuate wing vein dm-m and is transferred to Chrysosoma Guérin-Méneville, 1831 (comb. nov.). Chrysosoma ungulatum Parent, 1941 from Príncipe with an almost straight vein dm-m is transferred to Amblypsilopus (comb. nov.). Chrysosoma centrale Becker, 1923 from Tanzania also has a straight wing vein dm-m and modified fore tarsus, being very close in habitus to A. steelei Grichanov, 1996, and is also transferred to Amblypsilopus (comb. nov.). Chrysosoma asperum Parent, 1933 from South Africa has the same characters, is almost identical to South African A. bevisi and is also transferred here to Amblypsilopus (comb. nov.) and newly synonymized with A. bevisi (syn. nov.). Presently, 66 reliable species of Amblypsilopus are known from the Afrotropical region, including 37 from the Afrotropical mainland. A revised identification key to males of species of the Afrotropical mainland is provided. New records are given for some known species. The species diversity of the Afrotropical fauna and variability of morphological characters in the genus Amblypsilopus are briefly discussed.